20p12.3 microdeletion predisposes to Wolff–Parkinson–White syndrome with variable neurocognitive deficits. Issue 3 (23rd September 2008) - Lalani, S R; Thakuria, J V; Cox, G F; Wang, X; Bi, W; Bray, M S; Shaw, C; Cheung, S W; Chinault, A C; Boggs, B A; Ou, Z; Brundage, E K; et al.
Abstract : Background: Wolff–Parkinson–White syndrome (WPW) is a bypass re-entrant tachycardia that results from an abnormal connection between the atria and ventricles. Mutations in PRKAG2 have been described in patients with familial WPW syndrome and hypertrophic cardiomyopathy. Based on the role of bone morphogenetic protein (BMP) signalling in the development of annulus fibrosus in mice, it has been proposed that BMP signalling through the type 1a receptor and other downstream components may play a role in pre-excitation. Methods and results: Using the array comparative genomic hybridisation (CGH), we identified five individuals with non-recurrent deletions of 20p12.3. Four of these individuals had WPW syndrome with variable dysmorphisms and neurocognitive delay. With the exception of one maternally inherited deletion, all occurred de novo, and the smallest of these harboured a single gene, BMP2 . In two individuals with additional features of Alagille syndrome, deletion of both JAG1 and BMP2 were identified. Deletion of this region has not been described as a copy number variant in the Database of Genomic Variants and has not been identified in 13 321 individuals from other cohort examined by array CGH in our laboratory. Conclusions: Our findings demonstrate a novel genomic disorder characterised by deletion of BMP2 with variable cognitive deficits and dysmorphic features and show that individuals bearing microdeletions in 20p12.3 often present with WPW syndrome.